FINANCIAL TECHNOLOGY, BANK INTERMEDIATION, AND PERFORMANCE OF SMALL AND MEDIUM SCALE ENTERPRISES IN NIGERIA - Abiodun, Sopelola Tolulope; Ebenezer, Ariyibi Mayowa; O, Yinusa Ganiyu; O, Asogba Israel (Universitas Nusa Cendana, 2024)
The performance of the small and medium-scale enterprises is a function of internal and external factors, which are challenges for the enterprises to consider in their internal operations that spur the contribution to economic development. The inability to align with financial technology and the availability of bank intermediation prowess could retard their supposed contribution to economic development due to poor levels of performance. In the peculiarity of these challenges, this study examines the combined effect of financial technology and bank intermediation on small and medium-scale enterprises' performance. The study adopted time series data from the Central Bank Statistical Bulletin from 2019 to 2022 but was converted to quarterly data to accommodate the ordinary square least regression. The findings from the short-run results in accordance with the bound test revealed that point-of-sale, loan-to-deposit ratio, liquidity ratio, and interest rate have a positive significant effect on credit for small and medium-scale enterprises, while automated teller machines and deposit mobilization have a negative significant effect on credit for small and medium-scale enterprises. It is therefore recommended that financial institutions also reconsider their reliance on ATMs in SME operations, as it has a substantial negative impact. Encouraging web-based payment systems could also be beneficial, though further studies are needed to assess their full potential. Strengthening financial indicators like loan-to-deposit ratios and liquidity ratios should be prioritized to enhance credit provision. Additionally, financial institutions should explore alternative deposit mobilization strategies that do not constrain credit flow to SMEs. Keywords: Financial Technology; Bank Intermediation; SME’s Performance; Interest Rate